Kesiapan Guru IPA dalam Mengimplementasikan Pembelajaran Berbasis STEM di Madrasah Ibtidaiyah - Rizka Safitri; Siti Fatonah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
STEM-based education, integrating Science, Technology, Engineering, and Mathematics, is pivotal in equipping students with essential skills such as critical thinking, creativity, and problem-solving for the 21st century. This study explores the readiness of science teachers at Madrasah Ibtidaiyah to implement STEM-based teaching approaches. A qualitative methodology employing case studies and phenomenological design was applied, with data collected through interviews and questionnaires. Triangulation methods ensured the validity of findings. The research indicated that while science teachers demonstrated strong affective readiness (80%) and satisfactory cognitive preparedness (70%), their practical readiness (60%) and access to external support (50%) remain areas needing attention. Challenges included limited professional training, insufficient facilities, and difficulties in seamlessly integrating STEM elements into daily teaching practices. Recommendations from this study include regular, comprehensive training programs, improved infrastructure and resource support, and a phased implementation approach allowing teachers to develop STEM-based projects aligned with their students' needs and classroom conditions. This study underscores the untapped potential of science teachers to significantly improve STEM-based education at Madrasah Ibtidaiyah, provided there is robust institutional support and collaboration among stakeholders. The insights gained offer a valuable foundation for crafting inclusive policies to enhance teacher competencies and elevate educational quality at the elementary level.